Risk and financial management of COVID-19 in business, economics and finance - Chia-Lin Chang; Michael McAleer; Wing Keung Wong (Journal of Risk and Financial Management, 2020)
The SARS-CoV-2 coronavirus that causes the COVID-19 disease led to the most significant change in the world order over the past century, destabilizing the global economy and financial stock markets, the world's economy, social development, business, risk, financial management and financial markets, among others. COVID-19 has generated great uncertainty, and dramatically affected tourism, travel, hospitality, supply chains, consumption, production, operations, valuations, security, financial stress and the prices of all products, including fossil fuel and renewable energy sources. This Editorial introduces a Special Issue of the Journal of Risk and Financial Management (JRFM) on the "Risk and Financial Management of COVID-19 in Business, Economics and Finance". This Special Issue will attract practical, state-of-the-art applications of mathematics, probability and statistical techniques on the topic, including empirical applications. This paper investigates important issues that have been discussed in tourism, global health security and risk management in business as well as the social and medical sciences.
Keywords: 330; virus and disease; risk and financial management; business; economics and finance; tourism; global health security; social and medical sciences